A self-powered flexible humidity sensor and its preparation method and application
By using the self-powered flexible humidity sensor of the PVA/KOH/GO porous composite functional layer, the problem that sensing performance and power supply performance in the prior art are difficult to meet actual needs, and efficient and simplified humidity sensing and power supply functions are achieved.
Patent Information
- Application Number
- CN202411666725.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing flexible humidity sensors are difficult to meet the needs of practical applications in terms of sensing performance and power supply performance, especially voltage-based self-powered humidity sensors.
Using a porous composite functional layer composed of polyvinyl alcohol (PVA), potassium hydroxide (KOH) and graphene oxide (GO), the flexible substrate, the bottom electrode, the porous composite functional layer and the top electrode are laminated to achieve self-power supply. Preparation of flexible humidity sensors.
The sensor can effectively reduce power consumption, simplify sensing circuits, and improve sensing performance and power supply performance, achieving lossless in-situ sustainability monitoring of moisture information in the environment.
Smart Images

Figure CN119147593B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensor technology, and in particular to a self-powered flexible humidity sensor and a preparation method and application thereof. Background Art
[0002] As a basic wearable electronic device, flexible humidity sensors can effectively monitor humidity changes in the environment or on the surface of plants and animals, and show great application potential in many fields such as medical monitoring, human-machine interface, emotion analysis, sports activities and safe production. At present, flexible humidity sensors are mainly based on four types: capacitive, resistive, impedance and voltage. Among them, humidity sensors based on capacitive, resistive and impedance require external power supply, which will limit the service life of the device and cause environmental pollution problems. Flexible humidity sensors based on voltage do not require external power supply when working, which can effectively simplify the sensing circuit and better meet the requirements of low power consumption, miniaturization and integration. They have received widespread attention in the field of humidity sensing. However, the sensing performance and power supply performance of self-powered humidity sensors based on voltage are difficult to meet the needs of practical applications and need to be further improved. Therefore, the development of self-powered flexible humidity sensors is of great significance to the development of sensing technology. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a self-powered flexible humidity sensor and its preparation method and application. The self-powered flexible humidity sensor provided by the present invention can convert moisture information in the environment into electrical energy and realize the monitoring of moisture information, effectively reduce power consumption and simplify the sensing circuit, and provide a direction for the portable, miniaturized and integrated development of sensors.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a self-powered flexible humidity sensor, comprising a flexible substrate, a bottom electrode, a porous composite functional layer (PVA / KOH / GO) and a top electrode which are stacked in sequence, wherein the porous composite functional layer comprises polyvinyl alcohol (PVA), potassium hydroxide (KOH) and graphene oxide (GO).
[0006] Preferably, the mass ratio of the polyvinyl alcohol, potassium hydroxide and graphene oxide is 300:0-600:0.08, and the mass of the potassium hydroxide is not 0.
[0007] Preferably, the mass ratio of the polyvinyl alcohol, potassium hydroxide and graphene oxide is 300:30 to 300:0.08.
[0008] Preferably, the thickness of the porous composite functional layer is 200 nm to 1 μm.
[0009] Preferably, the thickness of the bottom electrode is 20-100 nm.
[0010] Preferably, the thickness of the top electrode is 200 nm to 0.05 mm.
[0011] Preferably, the flexible substrate is a polymer film, and the material of the polymer film is polyimide (PI), polydimethylsiloxane (PDMS) or polyethylene terephthalate (PET).
[0012] The present invention also provides a method for preparing the self-powered flexible humidity sensor described in the above technical solution, comprising the following steps:
[0013] Forming a bottom electrode on the surface of the flexible substrate;
[0014] Mixing polyvinyl alcohol, potassium hydroxide, graphene oxide and water to obtain a porous composite functional layer solution;
[0015] Coating the porous composite functional layer solution on the surface of the bottom electrode, and then drying to form the porous composite functional layer;
[0016] A top electrode is formed on the surface of the porous composite functional layer to obtain the self-powered flexible humidity sensor.
[0017] Preferably, the drying temperature is 85-130° C. and the drying time is 30-60 min.
[0018] The present invention also provides the application of the self-powered flexible humidity sensor described in the above technical solution in the field of real-time monitoring of moisture information.
[0019] The present invention provides a self-powered flexible humidity sensor, comprising a flexible substrate, a bottom electrode, a porous composite functional layer and a top electrode which are stacked in sequence, wherein the porous composite functional layer comprises polyvinyl alcohol, potassium hydroxide and graphene oxide.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] In the present invention, PVA has good adsorption and desorption effects on water molecules, and is a good choice as a power generation material for humidity generators. GO is a humidity sensitive material, which can ionize hydrogen ions by absorbing water. KOH has an adsorption effect on water molecules and can adsorb more water molecules. The porous composite film prepared by PVA, KOH and GO in the present invention ionizes hydrogen ions after absorbing water. The hydrogen ions are transferred due to the concentration gradient of the upper and lower surfaces of the porous film, thereby generating a voltage to realize self-powered humidity sensing. The present invention converts moisture information in the environment into electrical energy and realizes the monitoring of moisture information, effectively reduces power consumption and simplifies the sensing circuit, and provides a direction for the portable, miniature and integrated development of sensors, that is, the sensor prepared by the present invention can work without external power supply, and the generated voltage can also be used for external circuits, saving energy and protecting the environment; at the same time, the present invention takes PVA as the leading factor, and KOH and GO as doping materials to improve the performance of the PVA-based humidity sensor, which is of great significance to the realization of a high-performance voltage-based self-powered flexible humidity sensor; and the self-powered flexible humidity sensor device of the present invention has a simple structure and can be highly fitted with any surface.
[0022] Furthermore, the present invention limits the mass ratio of polyvinyl alcohol, potassium hydroxide and graphene oxide in the porous composite functional layer. Compared with traditional non-porous polymer films, it has a larger specific surface area and porosity. The porous structure is used to enhance the adsorption and dissociation of water by the film, which can greatly improve the absorption and dissociation rate of water by the device, effectively improve the output voltage / current, sensitivity, response / recovery time of the device, and comprehensively improve the sensing performance and power supply performance of the device, so as to prepare a humidity sensor with high sensitivity and wide humidity detection range, and realize in-situ non-destructive real-time sustainable monitoring of moisture information in the environment.
[0023] The present invention also provides a method for preparing the self-powered flexible humidity sensor described in the above technical solution. The preparation method of the present invention is simple and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the structure of the self-powered flexible humidity sensor of the present invention;
[0025] Figure 2 This is a working principle diagram of the self-powered flexible humidity sensor of the present invention;
[0026] Figure 3 The electrical performance diagram of the sensor of the comparative example;
[0027] Figure 4 This is a diagram of the electrical performance of the sensor of Example 1;
[0028] Figure 5 This is a diagram of the electrical performance of the sensor of Example 3;
[0029] Figure 6 The SEM microscopic morphology images of the functional layers of the comparative example and embodiment 1 are shown. DETAILED DESCRIPTION
[0030] The present invention provides a self-powered flexible humidity sensor, comprising a flexible substrate, a bottom electrode, a porous composite functional layer and a top electrode which are stacked in sequence, wherein the porous composite functional layer comprises polyvinyl alcohol (PVA), potassium hydroxide (KOH) and graphene oxide (GO).
[0031] Figure 1 It is a structural schematic diagram of the self-powered flexible humidity sensor of the present invention.
[0032] Figure 2 This is a working principle diagram of the self-powered flexible humidity sensor of the present invention. When the self-powered flexible humidity sensor is placed in an environment to work, the PVA / KOH / GO composite film adsorbs water molecules and ionizes hydrogen ions. As the water molecules gradually penetrate into the deep area of the porous composite functional layer, the hydrogen ions move in a directed manner driven by the concentration difference inside the film, and a potential difference is generated between the electrodes, outputting an electrical signal, thereby realizing non-destructive in-situ sustainable monitoring of moisture information in the environment.
[0033] In the present invention, the mass ratio of polyvinyl alcohol, potassium hydroxide and graphene oxide is preferably 300:0-600:0.08, more preferably 300:30-300:0.08, and most preferably 300:300:0.08.
[0034] In the present invention, the thickness of the porous composite functional layer is preferably 200nm~1μm, the porous composite functional layer has a large specific surface area and a highly adjustable porosity, has high adsorption capacity and selectivity, and can effectively adsorb gases and liquids; the porous composite functional layer can adsorb and dissociate water, and the porous composite functional layer ionizes hydrogen ions after absorbing water, and forms a concentration gradient inside the porous composite functional layer. Due to the concentration difference, the hydrogen ions migrate from high concentration to low concentration inside the porous composite functional layer, thereby generating a potential difference between the bottom electrode and the top electrode, and finally outputting an electrical signal.
[0035] In the present invention, the thickness of the bottom electrode is preferably 20-100 nm.
[0036] In the present invention, the thickness of the top electrode is preferably 200 nm to 0.05 mm.
[0037] In the present invention, the materials of the bottom electrode and the top electrode are preferably conductive films that can withstand a certain deformation, more preferably silver nanowires, carbon nanotubes or indium tin oxide (ITO); the material of the bottom electrode is preferably selected based on the deformation ability of the flexible substrate, and the electrode material with deformation ability matching the flexible substrate is selected; the material of the top electrode is preferably selected based on the electric potential between the top electrode and the bottom electrode and the process compatibility between the top electrode and each functional layer (including the flexible substrate, the bottom electrode and the porous composite functional layer).
[0038] In the present invention, the flexible substrate is preferably a polymer film, and the material of the polymer film is preferably polyimide, polydimethylsiloxane or polyethylene terephthalate.
[0039] The present invention also provides a method for preparing the self-powered flexible humidity sensor described in the above technical solution, comprising the following steps:
[0040] Forming a bottom electrode on the surface of the flexible substrate;
[0041] Mixing polyvinyl alcohol, potassium hydroxide, graphene oxide and water to obtain a porous composite functional layer solution;
[0042] Coating the porous composite functional layer solution on the surface of the bottom electrode, and then drying to form the porous composite functional layer;
[0043] A top electrode is formed on the surface of the porous composite functional layer to obtain the self-powered flexible humidity sensor.
[0044] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0045] The present invention prepares and forms a bottom electrode on the surface of a flexible substrate.
[0046] The present invention preferably uses a rigid substrate, and prepares the flexible substrate in the form of a flexible film on the rigid substrate.
[0047] In the present invention, the rigid substrate is preferably glass or silicon wafer.
[0048] In the present invention, the rigid substrate is preferably cleaned and surface treated in sequence before use and then used to prepare the flexible substrate.
[0049] In the present invention, the cleaning preferably includes the following steps: ultrasonically cleaning the rigid substrate in acetone, isopropanol and deionized water for 3 to 10 minutes respectively, and then drying it with nitrogen for later use.
[0050] In the present invention, the surface treatment preferably includes the following steps: firstly oxygen plasma treatment for 5 to 10 minutes, and then octadecyloctyltrichlorosilane (OTS) treatment for 10 to 20 minutes. The surface treatment is to facilitate the subsequent peeling of the flexible substrate from the rigid substrate and reduce deformation damage.
[0051] In the present invention, the octadecyloctyltrichlorosilane treatment preferably includes the following steps: in a clean petri dish, OTS and toluene are mixed in a volume ratio of 46 μL:20 mL, and then the substrate to be treated is placed therein, heated and fumigated for 20 to 30 minutes, and the treated sample is taken out and rinsed with toluene and isopropanol respectively, and then dried with nitrogen for later use.
[0052] In the present invention, the material for preparing the flexible substrate is preferably prepared into a uniform bubble-free solution, the solution is spin-coated or scraped on the rigid substrate, and then annealed in a vacuum environment to obtain the flexible substrate.
[0053] The present invention has no particular limitation on the specific parameters of the solution, spin coating, scraping coating and annealing treatment, and methods well known to those skilled in the art may be used.
[0054] The present invention preferably prepares the bottom electrode by magnetron sputtering, thermal evaporation or spraying process. The present invention has no special limitation on the specific parameters of the magnetron sputtering, thermal evaporation or spraying process, and the method familiar to those skilled in the art can be adopted.
[0055] In order to improve the adhesion between the flexible substrate and the bottom electrode, the flexible substrate is preferably treated with oxygen plasma before preparing the bottom electrode. The power of the oxygen plasma treatment is preferably 15 W and the time is preferably 10 min.
[0056] The present invention mixes polyvinyl alcohol, potassium hydroxide, graphene oxide and water to obtain a porous composite functional layer solution.
[0057] The present invention preferably mixes the polyvinyl alcohol with water to obtain a polyvinyl alcohol solution; mixes the potassium hydroxide with water to obtain a potassium hydroxide solution; mixes the graphene oxide with water to obtain a graphene oxide solution; and then mixes the polyvinyl alcohol solution, the potassium hydroxide solution and the graphene oxide solution to obtain the porous composite functional layer solution.
[0058] In the present invention, the concentration of the polyvinyl alcohol solution is preferably 50 mg / mL; the concentration of the potassium hydroxide solution is preferably 100 mg / mL; and the concentration of the graphene oxide solution is preferably 0.5 mg / mL.
[0059] In the present invention, the volume ratio of the polyvinyl alcohol solution, the potassium hydroxide solution and the graphene oxide solution is preferably 6:3:0.16.
[0060] After forming the bottom electrode and the porous composite functional layer solution, the present invention coats the porous composite functional layer solution on the surface of the bottom electrode and then dries it to form the porous composite functional layer.
[0061] In the present invention, the coating is preferably spin coating or blade coating.
[0062] In the present invention, the drying temperature is preferably 85-130° C., the drying time is preferably 30-60 min, and water is removed during the drying process.
[0063] After forming the porous composite functional layer, the present invention prepares a top electrode on the surface of the porous composite functional layer to obtain the self-powered flexible humidity sensor.
[0064] The present invention preferably prepares the top electrode by magnetron sputtering, thermal evaporation or spraying process. The present invention has no special limitation on the specific parameters of the magnetron sputtering, thermal evaporation or spraying process, and the method familiar to those skilled in the art can be adopted.
[0065] After forming the top electrode, the present invention preferably peels the flexible substrate from the rigid substrate to obtain the self-powered flexible humidity sensor.
[0066] In the present invention, the peeling preferably includes the following steps: firstly cutting along the edge of the joint position of the rigid substrate and the flexible substrate, and then prying up a corner of the flexible substrate and peeling it off obliquely.
[0067] The present invention also provides the application of the self-powered flexible humidity sensor described in the above technical solution in the field of real-time monitoring of moisture information.
[0068] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.
[0069] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0070] The PVA (Mowiol® PVA-210), KOH and GO used in the examples of the present invention were purchased from Aladdin.
[0071] Example 1
[0072] Fabrication of a self-powered flexible humidity sensor
[0073] Step 1: A rigid substrate is used to coat a flexible substrate in the form of a flexible film on the rigid substrate. The process is as follows:
[0074] Glass was used as the rigid substrate, and the size of the rigid substrate was 2.5 cm×1.0 cm.
[0075] The rigid substrate was cleaned, and the cleaning process was as follows: ultrasonically clean the rigid substrate in acetone, isopropanol and deionized water for 10 minutes respectively, and then blown dry with nitrogen for later use. The cleaned rigid substrate was surface treated, and the surface treatment process was as follows: firstly oxygen plasma treatment for 10 minutes, and then octadecyl octyl trichlorosilane treatment for 20 minutes. The process of octadecyl octyl trichlorosilane treatment was as follows: octadecyl octyl trichlorosilane treatment and toluene were mixed in a volume ratio of 46 μL: 20 mL in a clean culture dish, and then the substrate to be treated was placed in it, heated and fumigated for 20 minutes, and the treated sample was taken out and rinsed with toluene and isopropanol respectively, and blown dry with nitrogen for later use.
[0076] The flexible substrate preparation process is as follows:
[0077] On a cleaned and surface-treated rigid substrate, the PDMS stock solution and the cross-linking agent were mixed and stirred evenly in a mass ratio of 10:1, and the bubbles were removed by vacuuming, and the mixture was left to stand for use. Then, the solution of the flexible substrate material was coated on the rigid substrate by spin coating, and the prepared PDMS film was placed in a vacuum box for annealing at 80°C for 24 hours to obtain a flexible substrate in the form of a flexible film.
[0078] Step 2: Prepare a bottom electrode (thickness 20 nm) on a flexible substrate as follows:
[0079] The prepared flexible substrate was treated with oxygen plasma for 10 min at a power of 15 W. Subsequently, a 5 mg / mL Ag NW (silver nanowire) solution was spin-coated on the flexible substrate PDMS treated with oxygen plasma, and annealed (115°C, 5 min) to prepare a bottom electrode by coating on the flexible substrate.
[0080] Step 3: Prepare PVA solution, KOH solution and GO solution respectively, mix the three and apply them on the bottom electrode to prepare a porous composite functional layer (thickness 200nm), the process is as follows:
[0081] PVA solution (50 mg / mL, solvent is water), KOH solution (100 mg / mL, solvent is water) and GO solution (0.5 mg / mL, solvent is water) were mixed in the volume ratio of 6 mL: 3 mL: 160 μL to form a PVA / KOH / GO mixed solution. The mass ratio of PVA, KOH and GO was calculated to be 300: 300: 0.08. The PVA / KOH / GO mixed solution was spin-coated on a flexible substrate, and the prepared film was finally placed on a heating table at 85°C and dried for 60 minutes, thereby preparing a porous composite functional layer in the form of a flexible film on the bottom electrode.
[0082] Step 4: Coat the porous composite functional layer to prepare the top electrode (thickness 200 nm), the process is as follows:
[0083] A 5 mg / mL Ag NW stock solution was used as the top electrode material. The Ag NW stock solution was diluted and mixed with isopropanol to obtain a spraying solution. The volume ratio of the Ag NW stock solution to the isopropanol was 1:20.
[0084] Adjust the distance between the spray gun needle and the nozzle, place the flexible substrate with the bottom electrode and the porous composite functional layer on an 80°C heating table for preheating, fix the mask template on the surface of the porous composite functional layer and spray the solution, and perform annealing (annealing at 115°C for 5 minutes) after spraying to improve its conductivity to obtain the top electrode.
[0085] Step 5: Peel the flexible substrate off the rigid substrate to obtain a self-powered flexible humidity sensor based on the PVA / KOH / GO porous composite functional layer. The process is as follows:
[0086] Use a sharp blade to cut the flexible substrate along the four edges where the rigid substrate and the flexible substrate meet, then use tweezers to gently pry up a corner of the cut flexible substrate and clamp it with tweezers, then quickly peel it off along a 45° direction.
[0087] Example 2
[0088] Steps 1 to 3 and 5 are the same as those in Example 1, except that the preparation process of the top electrode in step 4 is different, as follows:
[0089] A 200 nm thick Al electrode was evaporated on the porous composite functional layer to complete the preparation of the top electrode.
[0090] Comparative Example PVA Film
[0091] Steps 1 to 5 are the same as those in Example 1, except that in step 3, a PVA solution is used, and no KOH solution and GO solution are added to form a PVA functional layer.
[0092] Example 3
[0093] Steps 1 to 5 are the same as those in Example 1, except that the blending mass ratios of PVA, KOH and GO in the composite film in step 3 are different. The specific process is as follows:
[0094] PVA solution (50 mg / mL, solvent is water), KOH solution (100 mg / mL, solvent is water) and GO solution (0.5 mg / mL, solvent is water) were mixed in a volume ratio of 6 mL:0.3 mL:160 μL to form a PVA / KOH / GO mixed solution. After calculation, the mass ratio of PVA, KOH and GO was 300:30:0.08.
[0095] The performance of the sensors prepared in the comparative example and embodiments 1 and 3 were tested. The specific method was as follows: a multimeter was used to collect the voltage and current signals of the sensor under different relative humidity conditions. Different relative humidity (RH) environments were obtained by a bubbling method and calibrated by a high-precision commercial humidity sensor. The relative humidity included 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 95%.
[0096] Figure 3 The electrical performance diagram of the sensor of the comparative example PVA film is shown in FIG. Figure 4 is the electrical performance diagram of the sensor of Example 1, Figure 5 This is the electrical performance diagram of the sensor of Example 3. It can be seen that after KOH and GO are added, the output voltage and response / recovery time of the device are affected to varying degrees. When the blending mass ratio of PVA, KOH, and GO is 300:300:0.08, the device performance is optimal, with an output voltage of ~700mV, a response time of 45s, and a recovery time of 34s.
[0097] Figure 6 The SEM microscopic morphology of the functional layer of the comparative example and Example 1 of the present invention shows that the surface of the pure PVA film is smooth and has no visible pore structure. After adding KOH and GO, obvious pore structure is observed on the film surface.
[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A self-powered flexible humidity sensor, characterized in that: Specifically, it comprises a flexible substrate, a bottom electrode, a porous composite functional layer and a top electrode which are stacked in sequence, wherein the porous composite functional layer comprises polyvinyl alcohol, potassium hydroxide and graphene oxide; and the mass ratio of the polyvinyl alcohol, potassium hydroxide and graphene oxide is 300:300:0.
08.
2. The self-powered flexible humidity sensor according to claim 1, characterized in that: The thickness of the porous composite functional layer is 200nm-1μm.
3. The self-powered flexible humidity sensor according to claim 1, characterized in that: The thickness of the bottom electrode is 20-100 nm.
4. The self-powered flexible humidity sensor according to claim 1, characterized in that: The thickness of the top electrode is 200nm~0.05mm.
5. The self-powered flexible humidity sensor according to claim 1, characterized in that: The flexible substrate is a polymer film, and the material of the polymer film is polyimide, polydimethylsiloxane or polyethylene terephthalate.
6. The method for preparing the self-powered flexible humidity sensor according to any one of claims 1 to 5, characterized in that: The following steps are involved: Forming a bottom electrode on the surface of the flexible substrate; Mixing polyvinyl alcohol, potassium hydroxide, graphene oxide and water to obtain a porous composite functional layer solution; Coating the porous composite functional layer solution on the surface of the bottom electrode, and then drying to form the porous composite functional layer; A top electrode is formed on the surface of the porous composite functional layer to obtain the self-powered flexible humidity sensor.
7. The preparation method according to claim 6, characterized in that: The drying temperature is 85-130° C. and the drying time is 30-60 min.
8. Application of the self-powered flexible humidity sensor according to any one of claims 1 to 5 in the field of real-time monitoring of moisture information.
Citation Information
Patent Citations
Self-powered flexible moisture sensor based on hydro-voltaic effect as well as preparation method and application of self-powered flexible moisture sensor
CN115266882A
Flexible self-powered humidity sensor based on zinc oxide piezoelectricity and preparation method thereof
CN117309940A